UNIVERSITY NOTES. (The Accounting Review, 1930)
This article presents information on happenings in several universities. In Boston University, Boston, Massachusetts Professor Henry J. Bornhofft is to be on sabbatical leave this year. Mr. James V. Toner is returning to the department after a year's absence. Mr. Arthur W. Johnson, New York University, has been appointed assistant professor in the department. The following promotions were made in the department: Edward J. Hyland, assistant professor, Charles H. Cornell, assistant professor, Raymond L. Mannix, associate professor. In University of California, Berkeley, California Mr. Paul A. Dodd, associate in economics, will be completing his work for the Ph.D. at Pennsylvania this year. Dr. Lewis A. Maverick is returning as lecturer in economics to assist in the fields of statistics and economic theory. Mr. Ira N. Frisbee was promoted to the rank of officiate professor. In University of Illinois, Chicago, Illinois Mr. C.B. Cox, assistant in accounting, is leaving to join the staff of Peat, Marwick, Mitchell and Co., Detroit. Mr. C.B. Larimore, Nebraska and W.H. Stout, Illinois, will be assistants this year. In University of Montana, Missoula, Montana Dean E.C. Line is teaching in the summer session at the University of California. Professor Sanford is doing research work in accounting with the Montana Power Co., making a special study of the federal water power requirements.